2018
DOI: 10.1186/s12882-017-0806-0
|View full text |Cite
|
Sign up to set email alerts
|

Engaging clinicians and patients to assess and improve frailty measurement in adults with end stage renal disease

Abstract: Background: The Fried frailty phenotype, a measure of physiologic reserve defined by 5 components (exhaustion, unintentional weight loss, low physical activity, slow walking speed, and poor grip strength), is associated with poor outcomes among ESRD patients. However, these 5 components may not fully capture physiologic reserve in this population. We aimed to ascertain opinions of ESRD clinicians and patients about the usefulness of the Fried frailty phenotype and interventions to improve frailty in ESRD patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 28 publications
1
17
0
Order By: Relevance
“…The most common form of prehabilitation includes exercise components with strength, aerobics, and stretching (62), although nutritional components (63)(64)(65) and psychological components (66) have been included. In a recent survey, both clinicians (97%) and patients (94%) agreed that pre-KT prehabilitation would help patients undergoing KT and that prehabilitation would make ESRD patients less frail (clinicians: 100% and patients: 84%) (67). Additionally, 97% of clinicians and 80% of patients agreed that patients would be interested in pre-KT prehabilitation (67).…”
Section: Unanswered Questionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common form of prehabilitation includes exercise components with strength, aerobics, and stretching (62), although nutritional components (63)(64)(65) and psychological components (66) have been included. In a recent survey, both clinicians (97%) and patients (94%) agreed that pre-KT prehabilitation would help patients undergoing KT and that prehabilitation would make ESRD patients less frail (clinicians: 100% and patients: 84%) (67). Additionally, 97% of clinicians and 80% of patients agreed that patients would be interested in pre-KT prehabilitation (67).…”
Section: Unanswered Questionsmentioning
confidence: 99%
“…In a recent survey, both clinicians (97%) and patients (94%) agreed that pre-KT prehabilitation would help patients undergoing KT and that prehabilitation would make ESRD patients less frail (clinicians: 100% and patients: 84%) (67). Additionally, 97% of clinicians and 80% of patients agreed that patients would be interested in pre-KT prehabilitation (67). However, a multi-center randomized controlled trial of prehabilitation among frail KT recipients is needed to confirm the efficacy of this intervention in preventing long-term outcomes and associated costs.…”
Section: Unanswered Questionsmentioning
confidence: 99%
“…Frailty has recently gained the attention of nephrologists, transplant surgeons, and renal health-care professionals for its promise of identifying vulnerable older patients living with end-stage kidney disease (ESKD) [1-6]. Frailty, originally identified in community-dwelling older adults, is defined as a medical syndrome of multisystem dysregulation and is manifested as a compromised resistance to stressors that increases vulnerability to dependence and mortality [7].…”
Section: Introductionmentioning
confidence: 99%
“…For example, a recent review of the literature by Cheng et al identified a growing body of evidence documenting improved outcomes in cardiopulmonary fitness with exercise training in patients after cardiothoracic and orthopedic surgeries, including post-cardiac transplantation [ 39 ]. There is also evidence that most nephrologists, geriatricians, transplant surgeons, and ESRD patients agree that prehabilitation could make ESRD patients less frail [ 40 ]. Because functional limitations can be improved through intervention, pre-KT risk assessment with the SPPB may provide an opportunity to intervene by encouraging patient participation in a prehabilitation program.…”
Section: Discussionmentioning
confidence: 99%